Ischemic Gangrene of the Glans following Penile Prosthesis Implantation - García Gómez, Borja (Hindawi Publishing Corporation, 2013)
The development of ischemic gangrene of the penis following implantation of prosthesis is unusual, and very few cases are available in the literature. As a result, no established treatment protocol is available. We report our experience within a case of gangrene of the glans following implantation of a three-component prosthesis. We present a 53-year-old male, smoker with diabetes and hypercholesterolemia, who underwent surgery for the insertion of a penile prosthesis with 3 components to correct his erectile dysfunction and severe Peyronie's disease. The procedure was carried out without incidents. During the postoperative period, the patient began to complain from penile and perineal pain. He developed avascular necrosis of the glans. The necrosed area was excised. Four weeks later, he developed fever and perineal pain arriving to the emergency room with the prosthesis extruding through the glans. He had emergency surgery to remove the prosthesis plus surgical lavage and was prescribed broad-spectrum antibiotic therapy. Four weeks later, the penis was completely revascularized and reepithelialized. Ischemic gangrene following penile prosthesis implantation takes place in patients with poor peripheral vascularisation. Diabetes mellitus has been the common denominator to all of the reported cases.